Efecto de la fertilización con lixiviados generados en el relleno sanitario del cantón Salcedo en el cultivo de papa chaucha (Solanum andigenum) - Lascano Reyes, Andrés Amilcar (2016)
We evaluated the effect of fertilization with leachate which was generated in the landfill of Salcedo Canton in the chaucha potato crop because in the province of Cotopaxi, Salcedo Canton ambiguously some farmers have taken the decision to fumigate their crops with this leachate. This study was conducted in Latacunga canton, Pusuchisi district, province of Cotopaxi. Our methodology in this research is causi-experimental study as it is the cause-effect of the independent variable by a field trial in order to determine the potato toxicologic residual that has been fertilized with leachate....